2015
DOI: 10.1007/s00454-015-9677-y
|View full text |Cite
|
Sign up to set email alerts
|

On Constant Factors in Comparison-Based Geometric Algorithms and Data Structures

Abstract: Many standard problems in computational geometry have been solved asymptotically optimally as far as comparison-based algorithms are concerned, but there has been little work focusing on improving the constant factors hidden in big-Oh bounds on the number of comparisons needed. In this thesis, we consider orthogonal-type problems and present a number of results that achieve optimality in the constant factors of the leading terms, including:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 58 publications
(55 reference statements)
0
9
0
Order By: Relevance
“…For d = 2 and d = 3 the results were recently strengthened with instance-optimal algorithms [4]. Chan and Lee [11] raised the question of determining the oracle complexity of skyline queries, and investigate the constant factors in the O(n log k) complexity for d = 2 and d = 3. For arbitrary values of d, Sheng and Tao recently showed that skylines can be computed in O(n log d−2 n) computational complexity with a minor adaptation of Kung et al's algorithm [31], thus removing a d 2 factor.…”
Section: Related Workmentioning
confidence: 97%
See 3 more Smart Citations
“…For d = 2 and d = 3 the results were recently strengthened with instance-optimal algorithms [4]. Chan and Lee [11] raised the question of determining the oracle complexity of skyline queries, and investigate the constant factors in the O(n log k) complexity for d = 2 and d = 3. For arbitrary values of d, Sheng and Tao recently showed that skylines can be computed in O(n log d−2 n) computational complexity with a minor adaptation of Kung et al's algorithm [31], thus removing a d 2 factor.…”
Section: Related Workmentioning
confidence: 97%
“…For d = 3, an upper bound of 2n log 2 n + O(n) comparisons follows from Kung et al's algorithm [31]; a lower constant factor than the naïve sorting approach, but one checks easily that Kung et al's algorithm does not guarantee better constant factors for oracle complexity than naïve sorting beyond d = 3. A bound of n log 2 k + O(n √ log k) was recently established [11], matching the information-theoretic lower bound of n log 2 k comparisons [28].…”
Section: Complexity Of Noiseless Skylinesmentioning
confidence: 97%
See 2 more Smart Citations
“…When d ∈ {2, 3}, the problem even admits "instance-optimal" algorithms [4]. [11] investigates the constant factor for the number of comparisons required to compute skyline, when d ∈ {2, 3}. The technique does not seem to generalize to arbitrary dimensions, and the authors ask among open problems whether arbitrary skylines can be computed with fewer than dnlogn comparisons.…”
Section: Contributionsmentioning
confidence: 99%